KNOWLEDGE ON ASSOCIATION OF CLINICALLY PROVEN ALLERGY WITH PETS AT HOME- A SURVEY - SharwiniBaskar,; N. , P. Muralidharan; S, Preetha. (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Rearing animals and birds at home is in practice in all cultures in the world; many families have a variety of pets. Pets are emotionally connected to family. Many pets have moved from outdoor protectors to indoor family members. When there is a high prevalence of pet keeping, pet allergens are also found relatively in higher concentrations. Humans are exposed to different kinds of allergies at least once in their lifetime. Some studies have shown that the frequency of allergic diseases has increased. Pet keeping was considered to be one of the risk factors for allergy development. Exposure to pet allergens in sensitive people causes diseases. Materials and method: An online and offline survey was conducted among 53 pet-keeping people. The data was collected, analyzed, and results were tabulated. Results: In this study, the results show 67.9% of the population participating have pets at home. 86.8% of the population have mostly dogs at their home. 52.8% of participant’s pets are staying outdoors. Conclusion: Animal danders are proven to be allergic to many clinical conditions. The study aims to associate allergy and having pets at home.